YouTube and New Visual Conventions Based on Editing - Martorell, Sandra (2024)
This work analyzes the new visual conventions on YouTube used by content creators with the aim of determining the editing techniques and resources they employ and comparing their techniques with the conventional rules of film editing. The initial hypothesis is that YouTubers have departed from the rules of classical film editing and have created their own editing code on YouTube. To study and demonstrate this phenomenon, the testimonies and videos of various lifestyle-themed content creators on YouTube are taken as the subject of analysis. The results conclude that the new creators of digital audiovisual content have developed their own editing approaches inspired by the emerging audiovisual trends of social media.